Geodemographic segmentation systems for screening health data. (December 1995) - Openshaw, S; Blake, M
Abstract : AIM--To describe how geodemographic segmentation systems might be useful as a quick and easy way of exploring postcoded health databases for potential interesting patterns related to deprivation and other socioeconomic characteristics. DESIGN AND SETTING--This is demonstrated using GB Profiles, a freely available geodemographic classification system developed at Leeds University. It is used here to screen a database of colorectal cancer registrations as a first step in the analysis of that data. RESULTS AND CONCLUSION--Conventional geodemographics is a fairly simple technology and a number of outstanding methodological problems are identified. A solution to some problems is illustrated by using neural net based classifiers and then by reference to a more sophisticated geodemographic approach via a data optimal segmentation technique.